Guidelines for developing safety measures for tourists of relevant authorities in Bangkok - Wiyapornt, Watcharawit; Srirungraung , Pimporn (Journal of Management Sciences Suratthani Rajabhat University, 2024)
Bangkok is a city with many tourist attractions to meet the needs of visitors. However, a diversity is a source of tourist insecurity. Good management can bring confidence and good image to tourists. This study aimed to study the implementation of safety measures as well as to find ways to develop safety measures of relevant authorities for tourists in Bangkok. The data was collected by in-depth interviews with 31 relevant agency representatives. Comments were made on current security actions as follows. 1) Strengths include systematic planning, budgeting and follow-up, the agent has knowledge and experience, public relations are communicated through online media. 2) Weaknesses include inadequate officers and lack of specialized expertise, integration of interagency cooperation, lack of engagement, and laxity in law enforcement. 3) Opportunities include tourists providing greater awareness of threat protection, technological advancements, and the government sees even greater significance and unrest in rival cities/tourist destinations. 4) Major obstacles include lack of clarity and practicality of policies. The original infrastructure was difficult to manage and budget constraints were in place. The results of the interviews involved in the analysis of such internal and external factors can be used as a plan for guidelines to improve operations. This includes, setting out plans and measures that are appropriate to the situation and specific to each area with a small but highly effective budget, such as getting communities involved, leveraging technology in communications and surveillance, as well as continuation of the integration of relevant agencies.